Analysis Of Land Erosion Hazard Level In The Babak River Watershed Using The Usle Method - Andari Putri, Ni Putu Ayu Satya; Setiawan, Ery; Suroso, Agus; Sulistiyono, Heri (Indonesian Journal of Multidisciplinary Science, 2025)
The Babak watershed is considered a high utility watershed that has strategic functions. With its very diverse functions, this watershed is not immune from various problems such as land conversion which results in critical lands, narrowing of river channels and sedimentation. Land degradation by erosion contributes an important role to high sedimentation. This research aims to calculate the amount of erosion and determine of erosion hazard level in the Babak watershed. To estimate the amount of erosion, the Universal Soil Loss Equation (USLE) method is used. The amount of erosion in the Babak watershed is assessed through the 9 weirs in the Babak watershed, namely Jengguar, Babak, Gde Bongoh, Keru, Simbe, Jurang Sate, Gebong, Datar and Baturiti weirs. The results of the analysis show that the amount of erosion that occurred at the weir was respectively 92,399 tons/ha/year, 86,828 tons/ha/year, 87,193 tons/ha/year, 72,074 tons/ha/year, 55,534 tons/ha/year, 112,123 tons/ha/year, 33,756 tons/ha/year, 32,935 tons/ha/year, and 34,073 tons/ha/year. Based on classification results is known that the dominant level of erosion hazard in the Babak watershed is very light to moderate. Gebong, Datar and Baturiti weirs are dominated by a very light erosion hazard level (I) with a total area spread of 56.889%, 59.715% and 67.13% respectively. Jengguar, Gde Bongoh, Keru and Simbe weirs are dominated by light erosion hazard level (II) with a total area spread of 41.454%, 42.272%, 45.684% and 49.468% respectively.